The Ecology of the Spoken Word : Amazonian Storytelling and the Shamanism among the Napo Runa - Uzendoski, Michael, 1968- (Book collections on Project MUSE., 2012)
The Ecology of the Spoken Word offers the first theoretical and experiential translation of Napo Runa mythology in English. Michael A. Uzendoski and Edith Felicia Calapucha-Tapuy present and analyze lowland Quichua speakers in the Napo province of Ecuador through narratives, songs, curing chants, and other oral performances, so readers may come to understand and appreciate Napo Runa aesthetic expression._x000B__x000B_Like many other indigenous peoples, the Napo Runa create meaning through language and other practices that do not correspond to the communicative or social assumptions of Western culture. Language itself is only a part of a communicative world that includes plants, animals, and the landscape. In the Napo Runa worldview, storytellers are shamans who use sound and form to create relationships with other people and beings from the natural and spirit worlds. Guiding readers into Napo Runa ways of thinking and being, Uzendoski and Calapucha-Tapuy weave exacting translations into an interpretive argument with theoretical implications for understanding oral traditions, literacy, new technologies, and language._x000B__x000B_Reinforcing the authors' argument that words are only a small part of storytelling reality, a companion website with photos, audio files, and videos of original performances offers readers an opportunity to more deeply understand the beauty of performance and complexity of sound in Native Amazonian verbal expression.